2017
DOI: 10.1080/23279095.2017.1363039
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional associations between metabolic syndrome and performance across cognitive domains: A systematic review

Abstract: This review aimed to systematically evaluate associations between the Metabolic Syndrome and domain specific cognitive performance from cross-sectional studies. PsycINFO and Medline were searched on 12 January 2017 with the terms "Metabolic Syndrome" and "cogni*." A total of 973 articles were identified, with 26 meeting inclusion criteria. Individuals with Metabolic Syndrome were consistently reported to have poorer performance on executive function tasks that were not adaptations of the verbal fluency task, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 64 publications
2
27
0
2
Order By: Relevance
“…We found that the executive function factor score was a significant moderator in the relationship between greater vascular risk and lower SPPB score and slower gait speed. This is consistent with prior findings of higher levels of cardiovascular risks and poorer performance on tasks purported to assess executive function (Alcorn et al, 2019;Rouch et al, 2014). Furthermore, there is substantial evidence supporting the important role executive function plays in controlling gait (Parihar, Mahoney, & Verghese, 2013), where decline in executive function is associated with gait dysfunction and slowing of gait (Mirelman et al, 2018;Montero-Odasso et al, 2012;Poole et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…We found that the executive function factor score was a significant moderator in the relationship between greater vascular risk and lower SPPB score and slower gait speed. This is consistent with prior findings of higher levels of cardiovascular risks and poorer performance on tasks purported to assess executive function (Alcorn et al, 2019;Rouch et al, 2014). Furthermore, there is substantial evidence supporting the important role executive function plays in controlling gait (Parihar, Mahoney, & Verghese, 2013), where decline in executive function is associated with gait dysfunction and slowing of gait (Mirelman et al, 2018;Montero-Odasso et al, 2012;Poole et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…ERPs enable us to index the time-course of critical processes for everyday cognition, including visual perception, categorization, and memory-related processes. We recorded ERPs while participants completed an executive function task, as performance in this domain appears particularly susceptible to cardiometabolic risk factors ( 18 , 20 , 21 ) and has been reported to be the earliest domain affected by cardiometabolic factors, with impairment in other cognitive domains becoming apparent as cardiometabolic and vascular diseases progress ( 22 , 23 ). We also took the summative cardiometabolic factor approach [similar to ( 12 , 13 )], given that individual risk factors rarely occur in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of community-dwelling older adults have observed that certain domains -perceptual motor function, language and memory -were consistently associated with frailty across studies [39][40][41] . A recent systematic review found that cross-sectional studies consistently reported that the metabolic syndrome was most consistently associated with reduced performance on executive function tasks, whereas associations with performance in attention/working memory/information processing, memory, language, and construction/motor performance domains were mixed 42 . Our results on the cognitive domains of immediate memory, delayed memory, and visuospatial/constructional ability highlighted the need for closer attention in specific areas of diabetes self-care or management such as medication adherence, self-monitoring of blood glucose and appointment keeping.…”
Section: Discussionmentioning
confidence: 99%